2019
DOI: 10.3390/met9010055
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Solidification in the Cast Mold with a Consumable Cooler Introduced Inside

Abstract: The microstructure is of great significance for the stability and mechanical performance of the cast slab. Recently, an innovative technology of feeding a consumable cooler into the mold has been proposed to improve the internal quality of castings. But the mechanism is not clear. In the present work, a water-cooled transparent laboratory equipment was set up and solidification of NH4Cl-70%H2O solution was studied to observe the in-situ growth and sedimentation of crystals. The experiments were conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…This is very helpful to facilitate central nucleation and growth of grain. [ 25,41 ] Additionally, similar to the 0.1 m s −1 case, there is also a decrease in LT4 due to flow field variation.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…This is very helpful to facilitate central nucleation and growth of grain. [ 25,41 ] Additionally, similar to the 0.1 m s −1 case, there is also a decrease in LT4 due to flow field variation.…”
Section: Resultsmentioning
confidence: 68%
“…[24,25,42] As the central equiaxed crystals continue to simultaneously nucleate, grow, and deposit, the region of the fine equiaxed dendrites at the bottom of the ingot and the vicinity of the strip gradually forms and increases in the area. [24,25,42] In addition, at the bottom of the ingot, the decrement in the superheating of the molten steel favors the formation of the deposited region of the equiaxed dendrites by inhibiting the melting back of the dendrites. [43,44] In contrast to the macroscopic structure of S1 ingot, the S2 ingot has a large number of fine equiaxed dendrites around the original strip and at the bottom.…”
Section: Validationmentioning
confidence: 99%
“…Zhao et al [12,13] conducted experiments with different initial temperatures and feeding ratios of steel strips using a similar method and compared the element composition, segregation, porosity, and inclusion distribution of billet under different parameters. To explore the effect of feeding strips on the microstructure of slabs, Liu and Niu et al [1,14] used an NH 4 Cl-70%H 2 O solution to study the growth process and morphology changes of dendrites under different "steel strips" sizes in the mold. However, although the phase transformation and microstructure growth process can be visually observed in the cold test, the physical properties of the test materials and metals are quite different.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] To overcome these problems, feeding strip technique (FST) has been developed to improve the internal quality of continuous cast slabs. [7] Extensive industrial tests and physical models have shown that FST can effectively eliminate porosity, [8,9] alleviate central segregation, [9][10][11][12][13][14] increase the equiaxial crystal ratio, [11][12][13][14][15][16] and improve surface cracks. [13] Up to now, FST has been gradually applied to improve the solidification quality of continuous cast slabs due to its low cost, simple setup, and superior efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Recently, the effects of process parameters on multiphysics field variations were mostly conjectured through industrial tests and physical models. [8,9,[11][12][13][14][15][16] In comparison, numerical simulation is a crucial tool for obtaining a deeper and more indirect understanding of the distribution of multiphysical fields. [19][20][21][22][23][24][25] Until now, only an extremely limited number of numerical models have been developed to study the multiphysical field during the FST process, [17,18,[26][27][28][29] and these models have been used to investigate the effects of strip feeding speed, [17,18,[26][27][28][29] strip size, [18] and molten steel superheat [18] on the temperature reduction after feeding strip during continuous casting process.…”
Section: Introductionmentioning
confidence: 99%